The Influence of Organizational Commitment as an Intervening Variable in the Relationship between Transformational Leadership, Work Motivation, and Employee Performance. - Oktofina Wafom; Filiph Karubaba (Proceeding of The International Conference on Business and Economics, 2026)
This study analyzes the influence of transformational leadership and work motivation on employee performance with organizational commitment as an intervening variable in public sector organizations. Using an explanatory quantitative approach, data were collected through a Likert scale questionnaire and analyzed with Partial Least Squares (SmartPLS) to test the direct and indirect effects between variables. The results show that transformational leadership and work motivation both have a positive and significant effect on employee performance; in addition, both also have a significant effect on organizational commitment. Organizational commitment was found to partially mediate the relationship between transformational leadership and work motivation with employee performance, so that the influence of leadership is dual (direct and indirect), while the influence of work motivation is strengthened when accompanied by an increase in organizational commitment. These findings reinforce the role of organizational commitment as an important psychological mechanism and recommend integrated managerial strategies to develop inspirational leadership, increase motivation, and build employee engagement to optimize performance in public institutions.